Desarrollo de un sistema inteligente deliberativo para controlar la población en el ganado vacuno. - León Ramón, Mario Richar (2016)
This research work is an alternative of improvement to the processes carried out in institutions engaged in livestock, breeding and cattle production, this alternative emerged from the need to improve the rate of population and control cattle. A major objective which includes the development of an intelligent web-based system deliberative agents to improve the rate of cattle population of villages, farms or small farms was established. To accomplish with the established objective, it was investigated about the processes and activities undertaken in livestock entities through internet searches and direct observation then the information collected was analyzed and priority was given to the processes needed to improve population index of beef cattle, these processes belong to the following sectors: reproduction, production, feeding and health, these sectors have many activities which have to be performed by technicians of the entities of livestock to each registered cattle. Finally, it was continued with the development of HatosGanaderos that provides a system of control and organization of Beef Cattle through modules; between them, there is information about the notes to give to the technicians on time to carry out the specific activity to each cattle. Currently all development must be based on a methodology to obtain better and timely results, for this reason to development the web system it was used the methodology called eXtreme Programming which gives the proper techniques to present to the user the advances of the functional system frequently and to make changes along the developing, and to the creation of deliberative agents the methodology GAIA which provide a flexible understanding of architecture, interaction and communication agents was used